Token Ekonomi Untuk Mengatasi Enuresis Non Organik Pada Anak - Husna, Kholidatul; Noviekayati, IGAA (Psycho Aksara : Jurnal Psikologi, 2023)
Enuresis is bed wetting behavior experienced by individuals who have gone through the developmental age of toilet training. This condition makes individuals and those around them experience problems in dealing with enuresis. The behavioral approach is an approach used to change maladaptive behavior into adaptive behavior. This approach is an effective therapy for children to carry out agreed behaviors to obtain the expected behavior. The token economy is a behavioral approach to giving tokens (signs) that focuses on modifying behavior to increase expected behavior and reduce unexpected behavior. Obtained tokens are collected in an agreed upon amount to be exchanged for prizes. Children with enuretic behavior can modify behavior using token economy techniques to anticipate enuretic behavior. The results of this study explain that the token economy can help overcome non-organic enuresis in children. Children are able to make changes in behavior according to the contract that has been planned together to avoid enuresis (wetting the bed).